RELIGIOSITY AND INTENTION TO ADOPT ISLAMIC FINANCING: INDIVIDUAL CONTROL AS A MEDIATOR? - Isnaini, Araina; Risna Wijayanti; Sumiati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Islamic Financing in Indonesia has not fully received the public's attention because the application of Islamic financing does not follow Sharia principles and Islamic law. This literature review aims to assist in understanding Islamic financing concerning the intention to use Islamic financing from the perspective of MSME owner-managers. Literature review method based on journals related to the keywords "attitude, subjective norms, perceived behavioral control, religiosity, Islamic financing" on the website https://scholar.google.com in the period 2013-2022. The results of previous research are summarized into four points: (1) most of the research was conducted in countries with Muslim majority populations; (2) the Theory of Planned Behavior was used as the theory underlying the research; (3) religiosity is an additional predictor because it is related to acceptance Islamic Financing by Muslim; and (4) the majority of research subjects are owner-manager of SMEs. The conclusion is the influence of individual assessment (attitudes) and social groups (subjective norms) affects individual control in the decision-making process by individuals. Religiosity may play a role in strengthening the relationship between individual assessment and social groups of perceived behavioral control. In the end, individual control influences the intention to use Islamic Financing.